Antiepileptic Treatment Strategy in Vascular Malformations - Giakoumettis, Dimitrios; Margetis, Konstantinos; Stranjalis, George; Haliasos, Nikolaos; Papaioannou, Theodoros G.; Themistocleous, Marios S. (Current Pharmaceutical Design, 2017)
Background: Antiepileptic treatment strategy plays an important role in the management of intracranial vascular malformations. The intracranial vascular malformations can be divided into cavernous hemangiomas, arteriovenous malformations, developmental venous anomalies and capillary telangiectasias. Seizures and hemorrhage are among their most common clinical manifestations. Objective: The aim of this article is to review the current literature on the antiepileptic treatment in the setting of intracranial vascular malformations and offer an updated view on when antiepileptic drug treatment should be employed for each type of vascular malformation. Methods and Materials: Current literature has been reviewed on cavernous malformations, arteriovenous malformations, developmental venous anomalies and capillary telangiectasias. Epidemiological features, epileptogenesis, clinical presentation and antiepileptic treatment have been analyzed. Results: A variety of treatment modalities exist for the management of intracranial vascular malformations, including antiepileptic treatment, microsurgery, radiosurgery and embolization. The decision-making process is different for each type of intracranial vascular malformation. Moreover, a plethora of other clinical factors needs to be taken into consideration during the decision-making process, such as the patient's age and comorbidities, the risk of hemorrhage the need for definitive treatment of the malformation, the seizure rates after the definitive treatment, the efficacy and side effects profile of antiepileptic drugs. Conclusion: Antiepileptic treatment strategy is a multifactorial decision that should be individualized and ideally be made by multidisciplinary teams.
Keywords: developmental venous anomalies